The immunobiology of Leishmania braziliensis infection - Brodskyn, Claudia I.; de Oliveira, Camila I. (Frontiers in Immunology, 2012)
Leishmaniases are a group of diseases caused by protozoa of the genus Leishmania that affect millions of people worldwide. These diseases are caused by distinct Leishmania species, of which L. braziliensis, a New World representative of the Leishmania genus, has been the least studied. Although leishmaniasis caused by L. braziliensis induces a range of clinical manifestations ranging from mild localized lesions to severe mucosal involvement, few studies have focused on elucidating the immune mechanisms behind this pathology. In this review, we focus on the immunobiology of L. braziliensis infection, emphasizing the innate and adaptive immune responses and taking into consideration both studies performed in endemic areas and experimental models of infection. Additionally, we address recent findings regarding the role of sand fly saliva in disease immunopathogenesis and vaccine development.